2015
DOI: 10.5897/ajar2014.9031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Erwinia chrysanthemi isolates inciting stalk rot disease of sorghum

Abstract: Stalk rot of sorghum plants caused by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Pectobacterium spp. proven to have the pectate degrading ability (Bhupendra and Yogendra, 2015), similarly, in the present study the isolates Ikg 2 and Icb 4 were found to degrade the sodium polypectate present in the CVP medium, leading to the formation of fissures in five days. Bacterial isolates were insensitive to erythromycin but sensitive to streptomycin.…”
Section: Kbsupporting
confidence: 81%
“…Pectobacterium spp. proven to have the pectate degrading ability (Bhupendra and Yogendra, 2015), similarly, in the present study the isolates Ikg 2 and Icb 4 were found to degrade the sodium polypectate present in the CVP medium, leading to the formation of fissures in five days. Bacterial isolates were insensitive to erythromycin but sensitive to streptomycin.…”
Section: Kbsupporting
confidence: 81%